Fatty acids composition of selected plant oils obtained from seeds and stones of fruits and their impact on human health - Mikołajczak, Natalia (Journal of Education, Health and Sport, 2018)
Introduction and aim: Oils are usually obtained (by pressing or extraction) from such plant raw materials as rapeseed, sunflower, flax and soy. Currently, there is an increasing interest among consumers of new types of oil obtained from non-traditional plant raw materials. A lot of attention is paid to seeds and stones of fruit, which are also the main by-product in the food industry. However, the use of seeds and stones of fruit as raw materials largely depends on the fat content and the fatty acid composition. Therefore, this article aims to collect literature data on the share of individual fatty acids in plant oils obtained from seeds and stones of fruits, also to present their impact on human health. Brief description of the state of knowledge: Literature data on the share of fatty acids in oils obtained from seeds of fruits such as apples, pears, red raspberries, and from stones such as sour cherries, plums, apricots, were collected in tables. On their basis, parameters such as minimum (MIN) and maximum (MAX) values, mean value (MV), standard deviation (SD) were determined, and the coefficient of variation (CV) for particular acids was estimated. The share of unsaturated acids in oils obtained from seeds and stones of fruit was over 88% (sour cherry stones oil) - 95% (red raspberry seeds oil). The share of C18:1 acid was in the range of 12.80% (red raspberry seeds oil) - 69.32% (plum stones oil), share of C18:2 acid 19.71% (plum stones oil) - 67.94% (apple seeds oil), and share of C18:3 acid 0.16% (plum stones oil) - 30.19% (red raspberry seeds oil). The share of saturated fatty acids in oils from seeds and stones of fruit was relatively low, in range of 4% (red raspberry seeds oil) - 12% (sour cherry stones oil), the main acid of this group was C16:0 acid (2.89% (red raspberry seeds oil) - 9.43% (sour cherry stones oil)). The share of other individual fatty acids from both this groups usually was lower than 1%. The ratio of fatty acids from n-3 and n-6 families ranged 1:1.75 (red raspberry seeds oil) - 1:237.76 (pear seeds oil). Summary: Analysis of the literature data showed that oils from seeds and stones of fruits are a valuable source of unsaturated fatty acids (they play many important functions in the human body), in particular C18:1 and C18:2 acids. The share of saturated acids is low, only C16:0 occurs in significant quantities. The ratio of acids from the n-3 and n-6 families in oils (except for red raspberry seeds oil) is unfavorable, this limits its use in the food industry.